2020
DOI: 10.1097/jom.0000000000001976
|View full text |Cite
|
Sign up to set email alerts
|

The Post Hurricane Harvey Respiratory Protection Training Program

Abstract: Objectives: This study evaluated the effectiveness of an outreach program which included safety training and the distribution of personal protection kits in the Houston area in the aftermath of Hurricane Harvey. Methods: Outreach : 71 volunteers conducted training sessions at 19 different sites and distributed a total of 1187 kits. Follow-up study : We conducted telephonic interviews to collect data on respiratory symptoms and obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Six months later, we re-contacted over 80 individuals who had received the safety training and assessed their health, the status of remediation efforts, and the effectiveness of the training. 5 Also, approximately 60 public health officials, faculty, staff, and students and nonprofit organization (eg, Fe y Justicia Worker Center) members participated in sponsored disaster response training events. Within 3 months of Harvey’s landfall, 201 soil samples and 38 water samples were collected from Houston-area neighborhoods and analyzed for 24 metals.…”
Section: Resultsmentioning
confidence: 99%
“…Six months later, we re-contacted over 80 individuals who had received the safety training and assessed their health, the status of remediation efforts, and the effectiveness of the training. 5 Also, approximately 60 public health officials, faculty, staff, and students and nonprofit organization (eg, Fe y Justicia Worker Center) members participated in sponsored disaster response training events. Within 3 months of Harvey’s landfall, 201 soil samples and 38 water samples were collected from Houston-area neighborhoods and analyzed for 24 metals.…”
Section: Resultsmentioning
confidence: 99%
“…12,26 Other studies that investigated the health effects of flooding on impacted populations reported increases in both respiratory and dermatological communicable diseases and prolonged psychological distress. [1][2][3][4][5][6][7][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In the aftermath of Hurricanes Katrina (2005), Rita (2005), Ike (2008), Sandy (2012), and Irma (2017), impacted individuals who sought medical care also reported fever, rash, gastrointestinal, and respiratory symptoms. 1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]27 These past studies describe the health-specific burdens due to flooding but simultaneously highlight the need to further understand both the overall and specific impacts of natural disasters such as hurricanes on susceptible individuals.…”
mentioning
confidence: 99%
“…Over the past decade, natural disasters have become increasingly more prevalent, more frequent in severity, and are more likely to induce detrimental health effects upon impacted populations 1–26 . In particular, the United States (US) has experienced numerous flooding events due to hurricanes and heavy rainfall both within coastal areas and further inland 12,26 . Specifically, more than 70% of presidential disaster declarations were attributed to flooding during the past decade 12,26 .…”
mentioning
confidence: 99%
See 2 more Smart Citations